Marxisme in hun bewoordingen - Trotski, Leon; Marx, Karl; Engels, Friedrich; Lenin, Vladimir Iljitsj ([S.l]: LSP, 2013)
"Leon Trotski, Karl Marx, Friedrich Engels, Vladimir Lenin DIGITAAL TE RAADLEGEN IN DE LEESZAAL"